Endogenous neurosteroids pregnanolone and pregnanolone sulfate potentiate presynaptic glutamate release through distinct mechanisms - Smejkalova, Tereza; Korinek, Miloslav; Krusek, Jan; Hrcka Krausova, Barbora; Candelas Serra, Miriam; Hajdukovic, Dragana; Kudova, Eva; Chodounska, Hana; Vyklicky, Ladislav (British journal of pharmacology, 2021)
BACKGROUND AND PURPOSE: Neurosteroids influence neuronal function and have multiple promising clinical applications. Direct modulation of postsynaptic neurotransmitter receptors by neurosteroids is well characterized, but presynaptic effects remain poorly understood. Here, we report presynaptic glutamate release potentiation by neurosteroids pregnanolone and pregnanolone sulfate and compare their mechanisms of action to phorbol 12,13-dibutyrate (PDBu), a mimic of the second messenger DAG. EXPERIMENTAL APPROACH: We use whole-cell patch-clamp electrophysiology and pharmacology in rat hippocampal microisland cultures and total internal reflection fluorescence (TIRF) microscopy in HEK293 cells expressing GFP-tagged vesicle priming protein Munc13-1, to explore the mechanisms of neurosteroid presynaptic modulation. KEY RESULTS: Pregnanolone sulfate and pregnanolone potentiate glutamate release downstream of presynaptic Ca2+ influx, resembling the action of a phorbol ester PDBu. PDBu partially occludes the effect of pregnanolone, but not of pregnanolone sulfate. Calphostin C, an inhibitor that disrupts DAG binding to its targets, reduces the effect PDBu and pregnanolone, but not of pregnanolone sulfate, suggesting that pregnanolone might interact with a well-known DAG/phorbol ester target Munc13-1. However, TIRF microscopy experiments found no evidence of pregnanolone-induced membrane translocation of GFP-tagged Munc13-1, suggesting that pregnanolone may regulate Munc13-1 indirectly or interact with other DAG targets. CONCLUSION AND IMPLICATIONS: We describe a novel presynaptic effect of neurosteroids pregnanolone and pregnanolone sulfate to potentiate glutamate release downstream of presynaptic Ca2+ influx. The mechanism of action of pregnanolone, but not of pregnanolone sulfate, partly overlaps with that of PDBu. Presynaptic effects of neurosteroids may contribute to their therapeutic potential in the treatment of disorders of the glutamate system.
Keywords: zvířata; Animals; HEK293 Cells; sírany; krysa rodu Rattus; Humans; Neurosteroids; Rats; pregnanolon; neurosteroidy; kyselina glutamová; HEK293 buňky; Pregnanolone; Sulfates; Glutamic Acid; lidé